2002
DOI: 10.1152/japplphysiol.00365.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in vasodilation in upstream muscle during intermittent pneumatic compression

Abstract: This study investigated the dosage effects of nitric oxide synthase (NOS) inhibitor N(G)-monomethyl-L-arginine (L-NMMA) on intermittent pneumatic compression (IPC)-induced vasodilation in uncompressed upstream muscle and the effects of IPC on endothelial NOS (eNOS) expression in upstream muscle. After L-NMMA infusion, mean arterial pressure increased by 5% from baseline (99.5 +/- 18.7 mmHg; P < 0.05). Heart rate and respiratory rate were not significantly affected. One-hour IPC application on legs induced a 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 64 publications
(68 reference statements)
4
48
1
Order By: Relevance
“…External mechanical compression has been shown to augment arterial flow regulation in upper and lower limbs (Bochmann et al 2005;Kirby et al 2005;Morris and Woodcock 2004;Tschakovsky et al 1996) and elicit significant vasodilation (Chen et al 2002;Clifford et al 2006). Present findings extend previous findings by demonstrating that external mechanical compression also reduces pulse wave velocity of the region compressed, suggesting a reduction in local artery stiffness.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…External mechanical compression has been shown to augment arterial flow regulation in upper and lower limbs (Bochmann et al 2005;Kirby et al 2005;Morris and Woodcock 2004;Tschakovsky et al 1996) and elicit significant vasodilation (Chen et al 2002;Clifford et al 2006). Present findings extend previous findings by demonstrating that external mechanical compression also reduces pulse wave velocity of the region compressed, suggesting a reduction in local artery stiffness.…”
Section: Discussionsupporting
confidence: 86%
“…This compression-related hyperemia may be related to local vasodilation of feed arteries (Chen et al 2002;Clifford et al 2006) in concert with venous emptying related to fall in capacitance vessel pressure during relaxation (i.e., muscle pump) (Tschakovsky et al 1996). Conditions that elicit smooth muscle relaxation are associated with concomitant reductions in arterial stiffness (Lemogoum et al 2004;Schmitt et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of change in eNOS mRNA expression is at odds with the results of previous investigations that employed a rat model of IPC (6,44). Tan et al (44) reported that application of compressions rapidly increased eNOS mRNA by up to 180% in the rat TA.…”
Section: Ipc-induced Changes In Mrna Expression Of Angiogenic Factorsmentioning
confidence: 85%
“…Although IPC application methods vary amongst studies in the literature, IPC has demonstrated some promise with regard to acute effects on vascular function. Indeed, in a rodent model, endothelial nitric oxide synthase (eNOS) mRNA expression and protein concentration have been shown to be significantly upregulated 4-h following a 1-h bout of IPC (Chen et al 2002;Tan et al 2006). However, in human application, although local hemodynamic shear stress is significantly increased during treatment, FMD and peak reactive hyperemic blood flow in the resistance arteries do not appear to be immediately improved following acute and chronic IPC application, respectively (Roseguini et al 2010;Sheldon et al 2012).…”
Section: Introductionmentioning
confidence: 99%